Production of high-energy-density fuels by catalytic beta-pinene dimerization: Effects of the catalyst surface acidity and pore width on selective dimer production - Jung, Ja Kyung; Lee, Yunsu; Choi, Jae-Wook; Jae, Jungho; Ha, Jeong-Myeong; Suh, Dong Jin; Choi, Jungkyu; Lee, Kwan-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
High carbon number hydrocarbon fuels were produced by catalytic beta-pinene dimerization. These fuels can be used as high-energy-density fuels, including diesel and jet fuels. To suppress the production of oligarners composed of more than two pinene units, which are undesirable in liquid fuels because of their high boiling temperatures and viscosities, the pore width of the silica-alumina aerogel catalysts was modified and their surfaces were treated chemically. The chemical treatment of the catalyst surface improved the selectivity of fuel-grade dimer production and suppressed oligomer formation. The reaction pathways for dimer production from pinenes were also studied. It was found that Bronsted acids are responsible for pinene condensation, although earlier works reported that Lewis acids are responsible for condensate formation. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ALPHA-PINENE; CATIONIC-POLYMERIZATION; ISOMERIZATION; BIOMASS; CHEMICALS; PERFORMANCE; CONVERSION; ALCOHOLS; LIMONENE; PURE